The artist's way a spiritual path to higher creativity - Cameron, Julia (Los Angeles, Calif. Jeremy P. Tarcher/Perigee, 1992)
"A comprehensive twelve-week program to recover your creativity from a variety of blocks, including limiting beliefs, fear, self-sabotage, jealousy, guilt, addictions, and other inhibiting forces, replacing them with artistic confidence and productivity."
Spiritual electricity : the basic principles -- The basic tools -- Week 1 : recovering a sense of safety -- Week 2 : recovering a sense of identity -- Week 3 : recovering a sense of power -- Week 4 : recovering a sense of integrity -- Week 5 : recovering a sense of possibility -- Week 6 : recovering a sense of abundance -- Week 7 : recovering a sense of connection -- Week 8 : recovering a sense of strength -- Week 9 : recovering a sense of compassion -- Week 10 : recovering a sense of self-protection -- Week 11 : recovering a sense of autonomy -- Week 12 : recovering a sense of faith.
Keywords: Creation (Literary, artistic, etc.); Self-actualization (Psychology)